Investigation of Fractalkine and MIP-1β Levels as Markers in Premature Membrane Rupture Cases: A Prospective Cohort Study - Şehmus Pala; Remzi Atılgan; Bünyamin Çim; Mehmet Kağan Açıkgözoğlu; Meryem Demir Can; Süleyman Cemil Oğlak; Nevin İlhan; Mustafa Yılmaz (Clinical and Experimental Obstetrics & Gynecology)
Background: To investigate fractalkine and MIP-1β levels in amniotic fluid and serum of cases with premature rupture of membranes. Methods: In this prospective cohort study, pregnant women who applied to the Firat University, Gynecology and Obstetrics Clinic with the diagnosis of premature rupture of membranes (PROM) between 24 weeks and 36+6 gestational weeks and who had elective cesarean section between 37–41 weeks of gestation were included. Amniotic fluid obtained during cesarean section and serum obtained from blood taken simultaneously from patients with cesarean section during sterile speculum examination in PROM cases were stored at –80 °C until the study day after the storage conditions were met. Tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β), interferon-gamma (IFN-γ), macrophage inflammatory protein-1 beta (MIP-1β) and fractalkine levels were measured by enzyme-linked immunosorbent assay (ELISA) from obtained serum and amniotic fluid samples. Results: There was no difference in age in both groups. Gravida, parity, gestational week, birth weight and umbilical artery pH values at birth were significantly higher in the control group than in the PROM group. Serum TNF-α, IL-1β, IFN-γ, MIP-1β and Fractalkine values were similar in both groups. However, while TNF-α values in amniotic fluid were similar in both groups, IL-1β, IFN-γ, MIP-1β and Fractalkine values were found to be significantly higher in the PROM group. Conclusions: Fractalkine and MIP-1β may be biomarkers worthy of investigation that can be used in the early diagnosis and prognosis of PROM cases.